Atuação fisioterapêutica na lesão medular em unidade de terapia intensiva: Atualização de literatura - Ferreira, Lucas Lima [UNESP]; Marino, Laís Helena Carvalho; Cavenaghi, Simone (Universidade Federal de Sao Paulo, 2012)
Objective. Collate and update knowledge in relation to physical therapy in spinal cord injury (SCI) in the intensive care unit (ICU). Method. We performed a literature update in the databases Lilacs, PubMed and Scielo, crossing the descriptors spinal cord injury, cinesiotherapy, physiotherapy, mobilization, rehabilitation, intensive care unit, respiratory therapy and electrotherapy in the period of 2005 to 2010. Results. We found 21 studies, however, only five articles met the inclusion criteria. Kinesiotherapy is essential since the phase of spinal shock, since it favors the maintenance of joint range of motion and flexibility, and to prevent circulatory complications caused/ resulted from prolonged immobilization in bed. Respiratory therapy promotes bronchial hygiene, correction of abnormal respiratory patterns and respiratory diseases. The electrotherapy is a feature still little used by physiotherapists in the intensive care units. Conclusions. The physical therapy in SCI in ICU is focused on motor rehabilitation through kinesiotherapy and intervention through the respiratory bronchial hygiene and training of respiratory muscles. New treatment modalities such as electrotherapy, there have been in intensive environment, there is a need for more studies to confirm benefits and risks of this feature in the spinal cord.
Physical therapy spinal cord injury in action in the intensive care unit: Update of literature
Keywords: Intensive care unit; Physical therapy modalities; Spinal cord injuries; artificial ventilation; electrostimulation therapy; human; immobilization; intensive care unit; kinesiotherapy; literature; mobilization; physiotherapy; respiratory tract disease; risk factor; spinal cord injury